FRI0081 Comparison of Disease Burden in Patients with Rheumatoid Arthritis (RA), RA with Secondary Osteoarthritis (OA), and OA in Routine Care. (15th July 2016) - Castrejon, I.; Chua, J.; Malfait, A.M.; Block, J.A.; Pincus, T.
Abstract : Background: Recent data indicate that the disease burden experienced by patients with osteoarthritis (OA) is similar to or greater than in rheumatoid arthritis (RA) 1 . Many patients with RA may have secondary OA, which may affect disease burden and clinical management. Objectives: To compare disease burden in patients with RA, RA with 2° OA, and OA, according to scores on a multi-dimensional health assessment questionnaire (MDHAQ) and physician RheuMetric checklist Methods: At one academic rheumatology center, all patients with all diagnoses complete an MDHAQ. The MDHAQ includes 0–10 scores for physical function (FN), pain (PN), and patient global estimate (PATGL), compiled into a 0–30 composite routine assessment of patient index data (RAPID3), and a 0–48 RA disease activity index (RADAI) self-reported joint count. In addition, physicians complete a RheuMetric checklist, which includes four 0–10 visual analog scales (VAS) for overall physician global (DOCGL), inflammation or reversible findings (DOCINF), damage or irreversible findings (DOCDAM), and patient distress unexplained by DOCINF or DOCDAM (e.g. fibromyalgia, depression) (DOCSTR). Patients were classified as RA, RA with 2° OA, and OA, according to medical record diagnoses. Measures were compared in the 3 groups by MANOVA, adjusted for age. Results: 669 patients seen in routine care between September 2014 and June 2015 were studied, including 248 with RA, 47 with 2° OA (16% of all RA), and 374 with OA. Patients with OA were significantly older, but no differences were seen in formal education or gender. MDHAQ scores indicated substantial disease burden in all 3 diagnosis groups, although least in RA patients with no 2° OA, intermediate in RA patients with 2° OA, and greatest in patients with primary OA, e.g., RAPID3 was 11.0±7.7, 12.3±6.7, and 15.1±6.3 in the 3 groups, respectively (Table) (p<0.001 adjusted for age). Among RheuMetric checklist scores, DOCGL did not differ significantly in the 3 groups; DOCDAM was higher than DOCINF in all 3 groups, but differed by 0.7 /10 units in RA vs 1.6 units in RA with secondary OA and 3.2 units in patients with primary OA (Table). Conclusions: Patients with OA appear to have a greater disease burden than those with RA; the disease burden is intermediate in RA patients who have 2° OA. The low DOCINF relative DOCDAM in RA patients may help explain why RA remission rates are well below 100% even though inflammation appears to be effectively controlled. Patient MDHAQ and physician RheuMetric are useful and feasible to assess and monitor rheumatic diseases in busy clinical settings References: C. El-Haddad, I. Castrejn, K. Gibson, Y. Yazici, M. Bergman, T. Pincus. Ann Rheum Dis 2015;74(Suppl2): 369. Tymms K, et al. Arthritis Care Res (Hoboken). 2014;66:190–6. Disclosure of Interest: I. Castrejon: None declared, J. Chua: None declared, A. Malfait: None declared, J. Block: None declared, T. Pincus Shareholder of: Health Report Services, Inc